Structure-property relationships of poly(vinylidene fluoride) induced by stress relaxation - Contreras Ramos, Maria Marjorie (2018)
Poly(vinylidene fluoride) have been utilized to carry out investigations on structure-property relationships. This polymer was relaxed at different temperatures (23, 80 and 120 ºC) and strains (3.5, 7 and 10%) during 24 h. The material, as processed and all relaxed conditions, was characterized by tensile tests, dynamic mechanical analysis (DMA) to determine mechanical properties; and solid-state nuclear magnetic resonance (NMR) and small angle X-ray scattering (SAXS) to detected morphological changes as a result of the stress relaxation. Tensile tests after stress relaxation showed a huge drop in the elastic modulus, varying from 30 to 45% compared to the as processed polymer. The NMR technique allowed to correlate the variation of the elastic modulus with the evolution of the structure inside the material, namely, decrease of crystalline fraction and increase of constrained amorphous region due to the stress relaxation. Nonetheless, the free amorphous fraction did not undergo a significant change. In addition, the SAXS measurements allowed to determine modifications of the structural parameters. It can be noted that the decrease of long period which was attributed to the decrease of amorphous layer thickness, as a result of the chains recoil. On the other hand, crystalline lamellar thickness did not change after stress relaxation at 23 ºC. However, at higher temperatures (80 and 120 ºC), the results showed the growth of the thickness of the crystalline layer due to crystallization by temperature activation. The structure evolution verified and described above occurred in nanoscale.